Jeopardy classroom instruction: Fostering students’ motivation to learn English vocabulary - Kusumaningrum, Widya Ratna; Binarti, Endang (JEES (Journal of English Educators Society), 2021)
The issue, dealing with gamification to foster learners’ motivation and vocabulary in learning English, has been investigated recently. It is perceived that gamification will directly affect the teaching-learning process and determine the learning ambiance. This study aims to shed light on the extent of the employment of Jeopardy Classroom Instruction to foster EFL learners’ motivation to learn English vocabulary. The study deployed an action research method with three phases of pre-cycle, cycle 1, and cycle 2. Pre-cycle was to document the initial classroom condition before using Jeopardy Classroom Instruction, while cycle 1 and cycle 2 were for knowing the teaching-learning process situation during the use of Jeopardy Classroom Instruction. The participants were junior high school students. The data were collected through observation, closed-ended questionnaire, and students’ score. The results suggested that Jeopardy Classroom Instruction is an adjunct to aid students’ motivation to learn vocabulary. It helped students to acquire self-belief, learning focus, the value of learning, study management, planning and monitoring and persistence. Also, it mitigated some motivation guzzlers such as learning anxiety, low control, failure avoidance and self-sabotage that might hinder them from learning vocabulary. HIGHLIGHTS: Jeopardy Classroom Instruction helped students to acquire self-belief, learning focus, the value of learning, study management, planning and monitoring and persistence. It mitigated some motivation guzzlers such as learning anxiety, low control, failure avoidance and self- sabotage that might hinder them from learning vocabulary.